Efficacy of a separate informed consent for anesthesia services: A prospective study from the Caribbean - Kavi Rampersad; Deryk Chen; Seetharaman Hariharan (Wolters Kluwer Medknow Publications, 2016)
Background and Aims: This study aimed to determine whether a separate written consent form improved the efficacy of the informed consent process for anesthesia in adult patients undergoing elective surgery at a tertiary care teaching hospital. Material and Methods: We randomized patients into two groups prospectively. The first group (Group A) signed the hospital's standard "Consent for Operation" form only while the second group (Group B) signed a separate "Consent for Anesthesia" form additionally. Patients were interviewed postoperatively with an eight-item questionnaire with responses in a 5-point Likert scale. A composite "adequacy of consent index" was generated from the responses and analyzed. Results: Two hundred patients (100 in each group) were studied. All patients indicated that the anesthesiologist(s) had their permission to proceed with their anesthesia care. The mean "adequacy of consent index score" in Group B was higher than that of Group A (30.6 ± 4.6 [standard deviation (SD)] vs. 27.9 ± 5.2 [SD]) (P < 0.001). The separate written consent had a positive impact on the patients' understanding of the nature and purpose of the intended anesthesia procedures (P = 0.04), satisfaction with the adequacy of information provided about common side effects (P < 0.001) and rare but serious complications (P = 0.008). Conclusions: A separate written consent for anesthesia improved the efficacy of the informed consent process with respect to better information about the nature and purpose of anesthesia, common side effects, and rare but serious complications.